The Influence of Low Birth Weight Infant Care on Child Development in the Working Area of East Langsa Health Center, East Langsa District Langsa City, Aceh Province in 2023 - Juliana Munthe; Henny Rista; Mastaida Tambun; Husmika Sari; Diah Wahyu Ningsih; Rosmega Pakpahan; Indra Manurung (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Low Birth Weight (LBW) infants are at high risk for complications and are one of the leading causes of infant mortality in Indonesia, including in Aceh Province, where infant mortality rates are significant. This study aims to analyze the impact of LBW infant care on child development in the working area of Langsa Timur Health Center, Langsa Timur District, Langsa City, Aceh Province, in 2023. The research used a qualitative approach, conducting interviews with mothers and infants with a history of LBW. Data analysis was performed descriptively using univariate analysis to identify the characteristics of mothers and infants, as well as child development. The results showed that the majority of mothers (80%) were under 35 years old, had secondary education (100%), and were housewives (100%). The majority of infants were female (60%), and most had appropriate development (60%). The majority of infants had a history of LBW (60%). The findings suggest that appropriate care for LBW infants plays a crucial role in supporting child development and is expected to contribute to efforts to reduce LBW rates and infant mortality in the region, as well as improving the quality of maternal and child healthcare services.